Penerapan Enterprise Risk Management (ERM) pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia: Analisis Sistematik Literatur dan Tantangan Implementasi - Aris Pransisco Siringo Ringo; Margaret Boru Siregar; Muhammad Aziz Malikul Mulki Muttaqin; Alvianus Kristian Sumual (Journal of Economic and Business Advancement, 2025)
This study aims to analyze the implementation of Enterprise Risk Management (ERM) in Micro, Small, and Medium Enterprises (UMKM) in Indonesia through a Systematic Literature Review (SLR) approach. The study reviewed various national and international literature discussing ERM practices in the culinary, agribusiness, and creative digital sectors during the period 2019–2025. The results of the study show that the implementation of ERM in UMKM is still partial and has not been strategically integrated into business processes. Most UMKM only implement the risk identification and mitigation stages, while the risk monitoring and evaluation aspects are not yet optimal. The level of ERM maturity varies between sectors, with agribusiness being relatively more advanced than the culinary and creative digital sectors. The main obstacles include low risk and digital literacy, limited human resources, and a lack of institutional support and national standard policies. This study emphasizes the need to strengthen an ERM framework that is adaptive to the characteristics of UMKM, improve managerial and technological capacity, and foster cross-actor collaboration to realize value-based and sustainable ERM.